Prognostic value of serum C-reactive protein in idiopathic multicentric Castleman disease and construction of a prognostic model for patients - Lei, Zhixiang; Wang, Ya; Yu, Tiantian; Zhang, Yiting; Cui, Wenting; Luo, Cancan; Luo, Qingqing; Zhou, Lili; Gao, Yuchen; Yu, Li (Frontiers in Medicine, 2025)
BackgroundIdiopathic Multicentric Castleman disease (iMCD) is a type of the rare lymphoproliferative diseases. C-reactive protein (CRP) is a well-recognized biomarker of inflammation, frequently exhibits elevated levels in individuals diagnosed with iMCD. However, its prognostic value of this factor in iMCD remains uncertain.MethodsThe clinical manifestations, biochemical information, treatment plan and overall survival time (OS) of 68 iMCD patients with basic information such as age, sex, time of first diagnosis, blood routine and serum CRP level data from 6 medical institutionsin China and abroad were retrospectively analyzed. The median follow-up time of the study was 44.47 months. The serum CRP level was divided into two groups according to the prognostic relationship by X-tile software, and then it was included in the risk model CRP-A for predicting death, together with the age of first visit > 60 years old, Hemoglobin (HGB) ≤ 80g/L, hepatomegaly and/or splenomegaly and plasma cell (PC) type. The predictive ability of the clinical model was evaluated by drawing calibration curve and ROC curve. The factors affecting the level of serum CRP were analyzed.ResultsUsing the Kaplan-Meier method, our analysis suggested that a higher serum CRP level (>26.8 mg/L) was associated with worse overall survival in patients (p = 0.004). We developed a multivariable prognostic model based on serum CRP levels to assess survival outcomes in iMCD. The discriminative performance of the model for mortality events was validated through calibration plots and receiver operating characteristic (ROC) curves highlighting CRP as a key biomarker associated with disease prognosis. Additionally, analyzing by chi-square test and Fisher’s exact test showed that age, B-symptoms, hypoalbuminemia, ECOG and plasma cell type were significantly associated with high serum CRP level in patients with iMCD, and that fibrinogen levels was positively correlated with CRP level.ConclusionHigh serum CRP levels are associated with a variety of clinical manifestations and laboratory abnormalities.